CONFLICT, ITS MANAGEMENT AND RESOLUTION - Mishra, Ashutosh (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Conflict is an inevitable aspect of human interaction, arising from diverse perceptions, goals, and values. This paper explores the multifaceted nature of conflict, encompassing both its origins and consequences within organizational settings. It emphasizes that conflicts often stem from incompatible goals and societal divisions, exacerbated by factors such as resource scarcity and identity differences. While conflicts can lead to negative emotions and hinder productivity, they also have the potential to spur innovation and foster collaboration when managed effectively. This study delves into various dimensions of conflict management, highlighting strategies that mitigate detrimental impacts while harnessing constructive outcomes. By analyzing both functional and dysfunctional effects, it underscores the importance of proactive conflict resolution in fostering healthier organizational climates. Ultimately, this paper advocates for a nuanced understanding of conflict as a catalyst for organizational growth and resilience.